68Ga-Labeled GX1 Dimer: A Novel Probe for PET/Cerenkov Imaging Targeting Gastric Cancer - Yin, Jipeng; Xin, Bo; Zhang, Mingru; Hui, Xiaoli; Chai, Na; Hu, Hao; Xu, Bing; Wang, Jing; Nie, Yongzhan; Zhou, Guangqing; Wang, Guanliang; Lu, Hongbing; et al. (Frontiers in Oncology, 2021)
Purpose: To synthesize the dimer of GX1 and identify whether its affinity and targeting are better than those of GX1. To prepare 68Ga-DOTA-KEK-(GX1)2 and to apply it to PET and Cerenkov imaging of gastric cancer. Methods: 68Ga-DOTA-KEK-(GX1)2 was prepared, and the labeling yield and stability were determined. Its specificity and affinity were verified using an in vitro cell binding assay and competitive inhibition test, cell immunofluorescence and cell uptake and efflux study. Its tumor-targeting ability was determined by nano PET/CT and Cerenkov imaging, SUV value, SBR quantification and a biodistribution study in tumor-bearing nude mice. Results: 68Ga-DOTA-KEK-(GX1)2 was successfully prepared, and the labeling yield was more than 97%. It existed stably for 90 min in serum. The binding of 68Ga-DOTA-KEK-(GX1)2 to Co-HUVECs was higher than that to HUVECs, BGC823 cells and GES cells. It was also higher than that of 68Ga-DOTA-GX1, indicating that the dimer did improve the specificity and affinity of GX1. The binding of KEK-(GX1)2 to Co-HUVECs was significantly higher than that of GX1. Additionally, the uptake of 68Ga-DOTA-KEK-(GX1)2 by Co-HUVECs was higher than that of 68Ga-DOTA-GX1 and reached a maximum at 60 min. Nano PET/CT and Cerenkov imaging showed that the tumor imaging of the nude mice injected with 68Ga-DOTA-KEK-(GX1)2 was clear, and the SUV and SBR values of the tumor sites were significantly higher than those of the nude mice injected with 68Ga-DOTA-GX1, indicating that the probe had better targeting in vivo. Finally, the biodistribution showed quantitatively that when organs such as the kidney and liver metabolized rapidly, the radioactivity of the tumor site of the nude mice injected with 68Ga-DOTA-KEK-(GX1)2 decreased relatively slowly. At the same time, the %ID/g of the tumor site was higher than that of other normal organs except the liver and kidney at 60 min, which indicated that the tumor had good absorption of the probe. Conclusion: GX1 was modified successfully, and the in vivo and in vitro properties of the GX1 dimer were significantly better than those of GX1. The imaging probe, 68Ga-DOTA-KEK-(GX1)2, was successfully prepared, which provides a candidate probe for PET and Cerenkov diagnosis of gastric cancer.